Concise dictionary of social and cultural anthropology - Morris, Mike (Michael Ashley) (Malden, Mass. ; Oxford : Wiley-Blackwell, 2012)
"The Concise Dictionary of Social and Cultural Anthropology is an accessible, hands-on guide to the hundreds of terms the student of anthropology and the general reader will encounter in dealing with anthropological and ethnographic literature. It includes related terminology from allied fields such as sociology, economics, and geography. The focus is on key concepts in anthropology, with a number of biographies included to identify influential figures who have formulated central theories and conducted the most famous field research within cultures around the world. Extensive bibliographical references provide pointers for further research. Anthropology is a relatively young discipline with a complex history. Anthropological research encompasses hundreds of cultures and provides a valuable perspective on an increasingly globalized world. Written by a researcher and librarian expert in the fields of social and cultural anthropology, this Concise Dictionary offers an invaluable reference to the terminology and accomplishments of this far-reaching and diverse field."--Page 4 of cover.
Concise Dictionary of Social and Cultural Anthropology; Contents; Acknowledgments; Introduction; List of Illustrations; concise dictionary of social and cultural anthropology; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Major Sources; References.
"Written by a researcher and librarian expert in the fields of social and cultural anthropology, this accessible, hands-on reference is designed to enlighten those newly engaged in anthropological study or seeking a quick guide to the field. Fills a need for a beginner's pocket guide to the far-reaching and complex field of anthropology, including over 800 detailed entries and the intellectual background of terms. Written in plain, accessible, jargon-free language, for readers without extensive background in the field. Features brief, conceptual definitions of terms, bibliographical references to anthropological classics, related works for background reading and further research. Offers a user-friendly format, including bold terms featured elsewhere in the book, extensive cross-references, and indexes of names, peoples, places and subjects. Includes related terminology from allied fields such as sociology, economics and geography."--Provided by publisher.
Includes bibliographical references (pages 280-308).
Print version record.
Keywords: Ethnology -- Dictionaries; Anthropology; Ethnology -- Dictionaries; Ethnology; SOCIAL SCIENCE -- Anthropology -- Cultural; Ethnology; Electronic books; Dictionaries